New additions to the genus Kisaura Ross (Trichoptera: Philopotamidae) from the Indian Himalaya - Pandher, Manpreet Singh; Saini, Malkiat Singh (Zootaxa, 2014)
Four new species of genus Kisaura Ross are added to the philopotamid fauna of India. The newly described species are K. holiensis sp. nov., K. holzenthali sp. nov., K. morsei sp. nov. (all from Uttarakhand) and K. golitarensis sp. nov. from Sikkim.